SUMO: ligases, isopeptidases and nuclear pores - Melchior, Frauke; Schergaut, Marion; Pichler, Andrea (Trends in biochemical sciences, 2003)
Small ubiquitin-related modifier (SUMO) proteins are reversibly coupled to numerous intracellular targets and modulate their interactions, localization, activity or stability. Recent advances in the SUMO field have uncovered the first SUMO E3 ligases and point to a complex family of isopeptidases. SUMO has been linked to many different pathways, including nucleocytoplasmic transport. Modifying enzymes and an isopeptidase have been detected at nuclear pore complexes. In addition, studies in yeast suggest a requirement of SUMO conjugation for nuclear protein import, and specific SUMO targets depend on modification for nuclear import or export.
Gesehen am 17.08.2023